Cost metrics of electrical energy storage technologies in potential power system operations - Nikolaidis, Pavlos; Poullikkas, Andreas (My University, 2018)
Modern power systems could not exist without the many forms of electricity storage that can be integrated at different levels of the power chain. In this work, the most important applications in which storage provides technical, economic and environmental benefits such as arbitrage, balancing and reserve power sources, voltage and frequency regulation, investment deferral, cost management and load shaping and leveling, are reviewed. Using a 5-function normalization technique the technical and operational characteristics relating to 18 electrical energy storage (EES) technologies are qualitatively assessed and the technology-application pairs identified across the power chain are presented. In particular, two functions were used to normalize the characteristics expressed in real units, two further functions were used for those in percentage values and one function was used to quantify the technical maturity. For large-scale/energy-management applications pumped hydro is the most reliable energy storage option over compressed-air alternatives whereas flywheel and electromagnetic EES devices are still focused on short-duration/power-based applications including frequency regulation, uninterruptible power supply, spinning reserve, etc. Encouraged by the appropriate market and regulatory structures, economics enable storing bulk electricity produced by intermittent sources connected to the grid, rather than using it at once. In medium-to-large scales advanced Pb-acid and molten-salt batteries are considered capable of storing distributed electricity, providing the advantage of load leveling of both the supply network and generation plant. In terms of safety and simplicity, Pb-acid and Li-ion systems are viable options for small-scale residential applications, giving consumers an incentive to reduce their time-of-use charges. Apart from their expected use in transportation sector in the forthcoming years, regenerative fuel cells and flow batteries may offer intriguing potential in stationary applications once mature to commercialization.
Keywords: Electricity markets; Electricity storage; Electricity storage cost metrics; Power economics; Power system operations